THE EFFECT OF WORK DISCIPLINE, WORK STRESS, AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE AT UD. BELLA DECORATION IN BADUNG REGENCY, BALI - Gustini, Ni Kadek Depi Ulan; Parwita, Gede Bayu Surya; Carina, Tiara (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2025)
The implementation of robust work discipline has been demonstrated to exert a substantial influence on the trajectory, effectiveness, and prevailing culture of an organization. In the context of any company or organization, the importance of work discipline cannot be overstated. Excessive work stress has been demonstrated to have a detrimental effect on an individual's well-being, manifesting in a decline in cognitive performance, particularly in the areas of concentration and problem-solving skills, within the professional context. Organizational culture is defined as a pattern of beliefs and values that are comprehended, assimilated, and enacted by an organization, thereby conferring a distinctive significance and serving as the foundation for regulations aimed at enhancing performance and conduct within the organization. The objective of this study is to elucidate the impact of work discipline, work stress, and organizational culture on employee performance at UD. Bella Dekorasi Kab. Badung Bali. The present study employs a quantitative research method, with primary data obtained from a questionnaire measured using a Likert scale. The population of this study comprised all 30 employees of UD. Bella Dekorasi Kab. Badung Bali. The data analysis employed in this study utilized Multiple Linear Regression Analysis, a statistical method, through the utilization of the SPSS application. The findings of the study indicate that work discipline exerts a positive and significant influence on employee performance. Conversely, work stress demonstrates a negative and substantial impact on employee performance. Moreover, organizational culture has been shown to have a positive and significant effect on employee performance.